Isolation of Ethylene Response Sensor Gene and Generation of Expressed Sequence Tags from the Oil Palm (Elaies Guineensis Jacq.) Mesocarp - Abdul Wahab, Nurniwalis (2006)
In this study, RT-PCR and partial sequencing of randomly selected cDNA clones were carried out to identify and hence lead to the isolation of a candidate mesocarp-specific gene from the oil palm. A 726 bp partial cDNA encoding an ethylene response sensor (ERS)-type ethylene receptor was first isolated by RT-PCR. Preliminary analysis via dot blot indicated that the partial cDNA showed very high expression in the oil palm mesocarp tissues with very low expression in the other tissues compared. Thus, ~ 1.1 kb partial cDNA (pER3RC A4) representing the 3’ end of the clone was isolated via 3’ RACE. Subsequently, three 17- week mesocarp cDNA libraries (GM17-1, GM17-5 and GM17-9) were successfully constructed. Based on the titer and average insert size, library GM17-5 was chosen for the generation of the ESTs. STACKpack clustering analysis generated 1011 unique transcripts comprising of 841 singletons and 170 consensus sequence representing 622 clones. Sequence homology searches against the non-redundant sequences in GenBank database revealed that approximately 48.0% of the clones had significant hits to other organisms (score > 50 and/or E value < 10-5). At least 10.2% of the ESTs have low similarity score whereas the remaining 41.8% had no match to other organisms in the public databases. The clones were found to have high sequence similarities to plant genes especially rice (34.9%) and Arabidopsis (20.3%). Majority (34.4%) of the clones were unable to be classified whereas 15.4%, 12.9% and 12.0% of the clones were categorized under cell rescue, defence and virulence, metabolism and protein synthesis, respectively. Two clones coding for a lipase class 3 family protein and an ethylene receptor (Q78EST) selected from the GM17-5 cDNA library were also found to show high differential gene expression in the mesocarp tissues via dot blot analysis. Alignment between Q78EST and pER3RC A4 indicated that they are highly similar to one another with 98% identity and with this information thus leads to the isolation and characterization of the full-length ethylene receptor gene. The full-length cDNA designated as EREG D3 is 2225 kb long and encodes a polypeptide of 629 amino acid residues. Northern and Southern analyses revealed that it is expressed highly in the mesocarp tissues as compared to the other tested tissues and that this gene exists as multi copy in the oil palm genome. Sequence analysis showed that EREG D3 has a structure similar to the bacterial two-component histidine kinase transduction system. These finding suggest that this gene may play an important role in plant signal transduction.